Small States in Global Affairs - Braveboy-Wagner, J. author. aut Link
V, 278 p.
Keywords: This book updates the 1989 volume 'Caribbean in World Affairs' providing a comprehensive and theoretically-grounded account of diplomatic developments in the Caribbean. The new material includes attention to the changed global setting, updated theoretical developments in foreign policy, and the inclusion of Haiti and Suriname.